Lifestyle Habits in Relation to Overweight and Obesity among Saudi Women Attending Health Science Colleges - Manan A. Alhakbany; Hana A. Alzamil; Wajude A. Alabdullatif; Shahad N. Aldekhyyel; Munirah N. Alsuhaibani; Hazzaa M. Al-Hazzaa (Springer, 2018)
The study examined the associations between lifestyle habits and overweight/obesity among Saudi females attending health science colleges. A total of 454 female students were randomly recruited from five health science colleges at King Saud University, using a multistage stratified cluster sampling technique. Body weight and height were measured, and body mass index was calculated. All participants answered a validated questionnaire to assess physical activity (PA), sedentary behaviors (SB), sleep duration, and dietary habits. Results showed that the prevalence of overweight (21.4%) plus obesity (8.1%) among female participants was 29.5%. There was no significant difference between overweight/obese and nonoverweight/nonobese females in PA, screen time, sleep duration, or dietary habits. Overall, 50.4% of the participants were physically inactive (activity energy expenditure was <600 metabolic equivalent minutes per week). Active females showed significantly (p < 0.01) higher intakes of vegetables and fruits, lower chocolate/candy consumption (p = 0.05), and higher proportion of sufficient sleeping duration (>8 hours per night) (p < 0.001). It was concluded that half of the Saudi females in this study were physically inactive. Although PA positively impacted some of the lifestyle habits of college females, overweight/obesity was not associated with PA, SB, sleeping time, or dietary habits among the participants. Future research should attempt to elucidate the key factors involved in such relationship.